BIOMASS PYROLYSIS KINETICS: A REVIEW OF MOLECULAR-SCALE MODELING CONTRIBUTIONS - Murillo,J. D. (2017)
Abstract Decades of classical research on pyrolysis of lignocellulosic biomass has not yet produced a generalized formalism for design and prediction of reactor performance. Plagued by the limitations of experimental techniques such as thermogravimetric analysis (TGA) and extremely fast heating rates and low residence times to achieve high conversion to useful liquid products, researchers are now turning to molecular modeling to gain insights. This contribution briefly summarizes prior reviews along the historical path towards kinetic modeling of biomass pyrolysis and focusses on the more recent work on molecular modeling and the associated experimental efforts to validate model predictions. Clearly a new era of molecular-scale modeling-driven inquiry is beginning to shape the research landscape and influence the description of how cellulose and associated hemicellulose and lignin depolymerize to form the many hundreds of potential products of pyrolysis.